RESEÑA de : López Sáenz, Mari Carmen. Investigaciones fenomenológicas sobre el origen del mundo social. Zaragoza : Universidad de Zaragoza, Prensas Universitarias, 1991 - Rodríguez Suárez, Luisa Paz (Investigaciones Fenomenológicas, 1995)
-